2016
DOI: 10.1111/jopy.12237
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Good Manners Rather Than Compassion Predict Fair Allocations of Wealth in the Dictator Game

Abstract: One of the most common tools for studying pro‐sociality is the dictator game, in which allocations to one's partner are often described in terms of altruism. However, the motivations driving these allocations may represent either emotional concern for others (compassion), adherence to social norms regarding fairness (politeness), or both. In this article, we apply personality psychology to the study of behavior in the dictator game, in which we examine the discriminant validity of distinct pro‐social construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 91 publications
11
73
0
Order By: Relevance
“…Studies across a range of areas have demonstrated the validity and utility of an aspect‐level analysis. Such studies reveal the differential relations that aspects within a domain have with threat processing (Cunningham, Arbuckle, Jahn, Mowrer, & Abduljalil, ), political ideology (Hirsh, DeYoung, Xu, & Peterson, ), fairness preferences (Zhao, Ferguson, & Smillie, ), and creative achievement in the arts and sciences (Kaufman et al, ). The aspects may similarly capture the key within‐domain divergences in predicting well‐being.…”
Section: Personality Traits and Three Taxonomies Of Well‐beingmentioning
confidence: 99%
“…Studies across a range of areas have demonstrated the validity and utility of an aspect‐level analysis. Such studies reveal the differential relations that aspects within a domain have with threat processing (Cunningham, Arbuckle, Jahn, Mowrer, & Abduljalil, ), political ideology (Hirsh, DeYoung, Xu, & Peterson, ), fairness preferences (Zhao, Ferguson, & Smillie, ), and creative achievement in the arts and sciences (Kaufman et al, ). The aspects may similarly capture the key within‐domain divergences in predicting well‐being.…”
Section: Personality Traits and Three Taxonomies Of Well‐beingmentioning
confidence: 99%
“…A substantial literature has highlighted the role of social norms, good manners, and individual differences in politeness in promoting prosocial behavior in economic games (Bolton et al, 1998;Camerer & Thaler, 1995;Guala & Mittone, 2010;Kimbrough & Vostroknutov, 2015;Zhao et al, 2016). However, the majority of these studies has concentrated on neutrally-framed games where there is an absence of contextual cues that guide real-world distributive decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to examine dictator decisions in situations where asymmetric distributions of wealth were normative and at odds with the equality norm. We were particularly interested in COMPASSION AND POLITENESS IN NORM-SALIENT DICTATOR GAMES 7 whether previous findings concerning the unique role of politeness (Zhao et al, 2016) would be replicated for dictator decisions when these were nested within equity and need norms.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations